2020
DOI: 10.1099/mgen.0.000415
|View full text |Cite
|
Sign up to set email alerts
|

Defining the transcriptional responses of Aspergillus nidulans to cation/alkaline pH stress and the role of the transcription factor SltA

Abstract: Fungi have developed the ability to overcome extreme growth conditions and thrive in hostile environments. The model fungus Aspergillus nidulans tolerates, for example, ambient alkalinity up to pH 10 or molar concentrations of multiple cations. The ability to grow under alkaline pH or saline stress depends on the effective function of at least three regulatory pathways mediated by the zinc-finger transcription factor PacC, which mediates the ambient pH regulatory pathway, the calcineurin-dependent CrzA and the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 67 publications
7
34
0
Order By: Relevance
“…A minor positive regulatory role for the salt activated transcription factor SltA on expression of ena genes has been shown in this and previous works 16 . This is in agreement with our RNA-seq results 10 , in which both enaA and enaB (but not enaC) were among the most intensely upregulated genes at pH 8 in a wild-type background (Top45 and Top2 genes with the highest log2FC values, respectively), but none of them was significantly downregulated in the sltAΔ mutant under these stress conditions.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A minor positive regulatory role for the salt activated transcription factor SltA on expression of ena genes has been shown in this and previous works 16 . This is in agreement with our RNA-seq results 10 , in which both enaA and enaB (but not enaC) were among the most intensely upregulated genes at pH 8 in a wild-type background (Top45 and Top2 genes with the highest log2FC values, respectively), but none of them was significantly downregulated in the sltAΔ mutant under these stress conditions.…”
Section: Discussionsupporting
confidence: 92%
“…the regulation of expression of ena genes in total RNAs isolated from mycelia grown at alkaline pH, in excess of Na + or Li + , and the mixture of high levels of either Na + or Li + with alkalinity. In agreement with previous results from Northern analyses 16,18 and RNA sequencing 10 , we confirmed that the expression of both enaA and enaB is regulated by these stresses. Under non stressing conditions (C, control condition), expression of enaA was detected and a positive effect was observed after addition of large amounts of Na + or Li + , or by alkalinizing the cultures (Fig.…”
Section: Transcriptional Regulation Of Ena Genes Series Of Northern supporting
confidence: 92%
See 1 more Smart Citation
“…Thus, I wondered what percentage of the potential A. nidulans TFome is transcribed as predicted and if there was a subset of genes rendering TF forms different from the predicted full-length forms or even non-functional. With that aim, RNA-seq experiments published by us previously [3133] and transcriptomic data available in the FungiDB database were used as a reference to compare genomic annotations and the most probable transcript sequences (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…B-E) Density of reads mapping to AN5078 (B), AN0396 (C), AN2392 (D) and AN2811 (E) loci . Images were exported using the IGV software (top; [31]) or from the JBrowse genome browser linked to the FungiDB database ( middle ). Bottom pictures correspond to BLAST searches at the NCBI website (panels B-D) or a Clustal alignment visualized with Genedoc (panel E).…”
Section: Resultsmentioning
confidence: 99%